SOUVENIR SALES FORECASTING ANALYSIS USING SUPPLY CHAIN MANAGEMENT APPROACH (CASE STUDY: SOUVENIR ORCHID SHOP) - Syarifuddin Syarifuddin; Nursalim Nursalim; Ivonne Ayesha; Eva Desembrianita (Jurnal Sistem Informasi, 2023)
Orchid Souvenir Shop is a business that provides various types of souvenirs and handicraft items. The purpose of the study is to forecast the stock of wedding souvenir products by empirically testing the facts or elements of the existence of supply chain management by analyzing industrial processes. Demand management activities need to be supported by the administration's systematic and easy demand forecasting process so that fast and accurate information can be obtained to support the MTO-based decision-making process (make-to-order). The demand forecasting method can reduce the risk of product obsolescence and unmet consumer needs and solve material supply problems. Decisions in supply chain management aim to reduce waste and optimize value for all components in the supply chain. Demand forecasting uses time series analysis with moving averages, exponential smoothing, and trend projection methods. To measure the accuracy of forecasting results, analysis using MSE, MAD, and MAPE is used.